Three dimensional response of RC bridges under spatially varying seismic excitation – numerical analysis and observations - Peña Ramos, Carlos Enrique; Haldar, Achintya (Journal of Structural Engineering, 2024)
The theoretical foundation of a procedure to estimate three-dimensional nonlinear time domain responses of bridges subjected to spatially varying seismic excitations (SVSE) presented in the companion paper is clarified further with the help of several informative examples. The procedure will satisfy the current design guidelines suggested in the International Building Code (IBC). Considering two piers in a bent and 3-, 6-, and 12- equal span bridges supported on the hard, medium, and soft soil conditions, the longitudinal and transverse responses of the bridges are estimated using the proposed method. The results are expressed in terms of rotational ductility demand (DD) at pier plastic hinge locations. The difference in responses between spatially varying and uniform seismic excitations is studied by introducing a new pier ductility index (DI) parameter by taking the ratio of the corresponding DD values. The near-field excitation is considered by increasing the vertical component of a design seismic wave. Several important observations are made for both far- and near-field excitations. For far-field condition, ignoring SVSE will typically result in the underestimation of the DD regardless of the length of the bridge and the type of soil under the piers. The underestimation could be as high as 64% for 12-span bridges supported on soft soil conditions. However, all piers in bridges considered in this study appear to satisfy AASHTO LRFD seismic design limitations on DD. The pier DD was found to be more sensitive to the variations in the types of soil under the piers than variations in the length of the bridges. The transverse DD values exceeded the longitudinal values for a significant number of piers in 3-span and 12-span bridges. Although the increases in pier DD were found to be relatively small for near-field excitation, the reduction in the pier ductility range can cause more piers to experience significant structural damage.